Positive Periodic Solutions for Impulsive Functional Differential Equations with Infinite Delay and Two Parameters - Zhenguo Luo; Liping Luo; Yunhui Zeng (Journal of Applied Mathematics)
We apply the Krasnoselskii’s fixed point theorem to study the existence of multiple positive periodic solutions for a class of impulsive functional differential equations with infinite delay and two parameters. In particular, the presented criteria improve and generalize some related results in the literature. As an application, we study some special cases of systems, which have been studied extensively in the literature.